KETERKAITAN ABNORMAL RETURN DAN TRADING VOLUME ACTIVITY PADA PERISTIWA PILKADA TAHUN 2015 - Rahma Nur Praptiwi (REMITTANCE: JURNAL AKUNTANSI KEUANGAN DAN PERBANKAN, 2021)
This research is an event study that aims to find out whether there is empiricalevidence of the reaction of the Indonesian capital market to political events inIndonesia, namely the 2015 Regional Head Election, using abnormal return indicators and trading volume activities. The population in this study are stocks that are included in the top 10 capitalization companies in Indonesia. The data used in this study is secondary data consisting of daily stock prices, daily stock trading volume, and daily stock price indexes for five days before and five days after the event. The statistical tool used to test the hypothesis is the paired sample t-test. The results of the statistical calculation of the paired sample t-test for both abnormal return and trading volume activity indicate that there is no difference in the average abnormal return and trading volume activity before and after the event.